Are food labels effective as a means of health prevention? - Gaia Claudia Viviana Viola; Francesca Bianchi; Elia Croce; Elisabetta Ceretti (SAGE Publishing, 2016)
Chronic diseases related to unbalanced and unhealthy eating habits have definitely become one of the major issues of modern age, not only in western countries but also in those ones where rapid economic growth has increased global prosperity levels. In order to avoid medical systems to collapse under excessive costs, International and Public Organizations strongly support health policies that aim to make people shift towards wholesome dietary patterns, also encouraging the use of food-labels to choose healthier products. To evaluate the consumers' knowledge and perception about food-labels a brief questionnaire was developed and shared on Facebook between January-March 2016. Most of the participants were young adults with higher education. They declared to do their shopping at least once a week, reading the foodlabels quite often. Despite owing limited knowledge in basic nutrition principles and food-labelling they were generally able to recognize healthier products looking over their nutritional fact tables. Anyway, on average, what they care the most about the products they purchase is the global quality level rather than the nutritional values. In order to induce the whole population to use food label as an effective self-protection tool, more efforts should be done to improve their knowledge on nutrition fundamentals and basics about food labelling, because that would make them able to take safer and more conscious choices as regards their own health.